Gomphonema bicepiformis sp. nov., a new diatom species (Bacillariophyta) from a stream in Zhejiang, China - Zhang, Wei; Shang, Guangxia; Kociolek, Jhone Patrick; Wang, Liqing; Tan, Hongxin (Phytotaxa, 2018)
During a survey of freshwater diatoms from Shibadukeng stream in the Xianju County, Zhejiang Province, China, a new gomphonemoid species, Gomphonema bicepiformis sp. nov. has been recorded. The new species is diagnosed from all others in the genus based on morphology as observed with both light and scanning electron microscopy. Valves of Gomphonema bicepiformis are lanceolate with a gibbous central region. The headpole is broadly rounded, clearly capitate and the footpole is also broadly rounded, capitate. The axial area is wide, lanceolate-rhombic, broad at mid-valve, reaching 3/4 of the total breadth. There are circular to irregularly-shaped depressions in the axial area on the exterior of the valve surface often appearing as light spots in LM. The new species was compared with G. biceps, G. obstipum, G. manubrium, G. pyrenaicum, G. guayabense and G. nipponica, all of which resemble Gomphonema bicepiformis in outline, but differ from the new species in specific details of size, striae density, and extent of the axial area. This species occurs in relatively low conductivity and clean water in Zhejiang, China.